The relationship between digital competence and job satisfaction and loyalty of lecturers in vietnamese higher education institutions - Do Thi, Y Nhi; Phuong, Huynh Cong; Hue, Khuong Thi (Technium Business and Management, 2025)
The study aims to clarify the relationship between faculty members’ digital transformation competency and two key factors in the higher education environment: job satisfaction and organizational loyalty. Building upon foundational theories and prior empirical studies, the research proposes a theoretical model comprising four core components of digital transformation competency: digital technology proficiency, digital pedagogy competency, digital research competency, and digital management competency. Based on this model, a set of research hypotheses was developed and an empirical survey was conducted with 250 university lecturers. Through a series of quantitative analyses, including Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM), the study empirically examined the relationships among the variables. It also assessed the mediating role of job satisfaction in the linkage between digital transformation competency and faculty loyalty. The findings not only confirmed the mediating role of job satisfaction but also highlighted the profound and positive impact of digital transformation competency on lecturers’ work motivation and professional commitment. These findings contribute to the theoretical foundation of digital transformation in higher education and offer important managerial implications for educational administrators and policymakers. Specifically, the study provides practical suggestions for the development of training policies, faculty development strategies, and retention initiatives in the context of comprehensive digital transformation—ultimately enhancing the quality and sustainability of Vietnam’s higher education system.